Outcomes of normothermic machine perfusion of liver grafts in repeat liver transplantation (NAPLES initiative). Issue 4 (15th February 2022) - Hann, A.; Lembach, H.; Nutu, A.; Dassanayake, B.; Tillakaratne, S.; McKay, S. C.; Boteon, A. P. C. S.; Boteon, Y. L.; Mergental, H.; Murphy, N.; Bangash, M. N.; Neil, D. A. H.; et al.
Abstract: Background: Retransplantation candidates are disadvantaged owing to lack of good-quality liver grafts. Strategies that can facilitate transplantation of suboptimal grafts into retransplant candidates require investigation. The aim was to determine whether late liver retransplantation can be performed safely with suboptimal grafts, following normothermic machine perfusion. Methods: A prospectively enrolled group of patients who required liver retransplantation received a suboptimal graft preserved via normothermic machine perfusion. This group was compared with both historical and contemporaneous cohorts of patient who received grafts preserved by cold storage. The primary outcome was 6-month graft and patient survival. Results: The normothermic machine perfusion group comprised 26 patients. The historical (cold storage 1) and contemporaneous (cold storage 2) groups comprised 31 and 25 patients respectively. The 6-month graft survival rate did not differ between groups (cold storage 1, 27 of 31, cold storage 2, 22 of 25; normothermic machine perfusion, 22 of 26; P = 0.934). This was despite the normothermic machine perfusion group having significantly more steatotic grafts (8 of 31, 7 of 25, and 14 of 26 respectively; P = 0.006) and grafts previously declined by at least one other transplant centre (5 of 31, 9 of 25, and 21 of 26; P < 0.001). Conclusion: In liver retransplantation, normothermic machine perfusion can safely expand graft options without compromising short-term outcomes. Lay Summary: Liver transplantation is a life-saving procedure for many different diseases. In the UK, one in 10 patients awaiting transplant have had a previous liver transplant. These retransplant operations are complex, and the general belief is that a good-quality donor liver graft is required for best outcomes. However, there is a significant shortage of good-quality organs for liver transplantation, so many patients awaiting retransplantation spend longer on the waiting list. This study investigated whether a new technology, called normothermic machine perfusion, could be used to preserve lower-quality donor livers and have successful outcomes for patients undergoing retransplantation. Traditionally, good-quality livers are preserved in an ice box and the study compared the outcomes of these two different approaches. The aim was to prove that normothermic machine perfusion improves access to transplantation for this group of patients, without compromising outcomes. A group of patients who underwent retransplantation and received a lesser-quality liver preserved with normothermic machine perfusion was compared with two groups of patients who had received a transplant with traditional ice-box preservation. The complications, graft, and patient survival of the former group was compared with those in the latter two groups who underwent liver retransplantation with better-quality liver grafts. The rate of survival and adverse surgical outcomes were comparable between the groups of patients who received a liver preserved via traditional ice-box preservation, and those who received a lesser-quality liver preserved via normothermic machine perfusion. Normothermic machine perfusion can potentially expand the number of suitable donor livers available for retransplant candidates. Abstract : In this study, liver grafts that underwent normothermic machine perfusion were compared with those that had static cold storage preservation, in the setting of liver retransplantation. Despite a lower organ quality in the machine perfusion group, the outcomes were comparable. Therefore, machine perfusion can be used safely to expand the pool of organs suitable for liver retransplantation.